DETERMINANTS OF MSMEs SUSTAINABILITY MODERATED BY GOVERNMENT POLICY ON MSME IN BATAM CITY - Prima, Argo Putra; Tipa, Handra; Syukrina E. Janrosl, Viola; Satria , Robby; Mulawarman, Mulawarman; Yusuf, Muhammad (Universitas Putera Batam, 2025)
This research was conducted at the Cooperative and SME Office of Batam City, with the survey location covering all business actors registered with the Cooperative and SME Office of Batam City. Based on the research results, there is a positive and significant influence between digital literacy and the effectiveness of digital accounting among SMEs in Batam City. High digital literacy helps organizations understand, implement, and use technology more effectively, in accordance with the TOE framework. There is a positive and significant influence between relative advantage and the effectiveness of digital accounting among SMEs in Batam City. The effectiveness of using digital accounting for SMEs, especially those in Batam City, is particularly viewed from the perspective of relative advantage. There is a positive and significant influence between competitive pressure and the effectiveness of digital accounting among SMEs in Batam City. These findings provide a better understanding of how competitive pressure plays an important role in increasing the use of digital accounting technology in the MSME sector. There is a positive and significant influence between compatibility and the effectiveness of digital accounting among MSME actors in Batam City. This research can provide a comprehensive picture of how the factor of compatibility plays a crucial role in the effectiveness of digital accounting use among SMEs, focusing on aspects that can certainly help SMEs make better decisions regarding the implementation, application, and development of digital accounting technology. Digital literacy, relative advantage, competitive pressure, and compatibility influence the effectiveness of digital accounting for MSME actors in Batam City.